1994
DOI: 10.1111/j.1467-8624.1994.tb00738.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relations of Emotionality and Regulation to Children's Anger-related Reactions

Abstract: The purpose of this study was to examine the relations of emotionality (intensity and negative emotion) and regulation (attentional control, mode of coping) to preschoolers' naturally occurring anger reactions. School personnel's ratings of 4-6-year-olds' constructive coping and attentional control were associated with boys' constructive anger reactions whereas their ratings of acting out versus avoidant coping, emotional intensity, and anger intensity generally were correlated with low levels of constructive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
1
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(118 citation statements)
references
References 52 publications
5
107
1
3
Order By: Relevance
“…It may be more appropriate to examine the children's AR under more ecologically valid situations such as in their school or home rather than through laboratory analogues of the type employed here. Employing both paradigms and multiple informants, as Eisenberg et al (1994) did with typical children, might be the approach to follow in future research.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It may be more appropriate to examine the children's AR under more ecologically valid situations such as in their school or home rather than through laboratory analogues of the type employed here. Employing both paradigms and multiple informants, as Eisenberg et al (1994) did with typical children, might be the approach to follow in future research.…”
Section: Discussionmentioning
confidence: 98%
“…Mangelsdorf, Shapiro, and Marzolf (1995) reported individual differences in the acquisition and use of AR strategies and that children acquire a wider range of increasingly complex AR strategies, as they mature. Eisenberg, Fabes, Nyman, Bernzweig, and Pinuelas (1994) found that the effects of emotionality and regulation were also related to more constructive reactions to anger with increasing age. Constructive reactions in their study were those that aimed at problem solving and were least disturbing to others.…”
Section: Introductionmentioning
confidence: 93%
“…Young children who are less able to voluntarily shift their attention and inhibit their impulses have higher levels of aggressioñ Rothbart, Ahadi, & Hershey, 1994!. In contrast, children with good attentional control are able to shift attention away from angerinducing cues, use nonhostile verbal methods, and function more appropriately in conflict situations~Eisenberg et al, 1997;Eisenberg, Fabes, Nyman, Bernzweig, & Pinuelas, 1994!. Inhibitory control contributes to the development of conscience in young school-aged children~Kochanska, Murray, & Coy, 1997!, and children's self-control fosters a sense of responsibility for their actions~Derryberry & Reed, 1996!. In these and related studies, behavior regulation and emotion regulation are considered extensions of a more fundamental capacity for executive or "effortful" control Rothbart, 1998, 2000!, anddecrements in this regulatory capacity are thought to be responsible for aggressive behavior problems~see Hill, 2002, for a review!.…”
Section: Emotion Regulation Executive Control and Aggressive Behaviormentioning
confidence: 96%
“…Using a 7-point Likert scale, parents rate how likely they are to respond in each of these ways. The responses yield six subscales (minimizing reactions, punitive reactions, distress reactions, expressive encouragement, problem-focused responses, emotion-focused reactions) with adequate psychometric properties [48][49][50][51]. To reduce the number of analyses conducted and because of theory linking particular subscales, the minimizing reactions, punitive reactions, and distress reactions subscales were combined to form a composite measure of mothers' unsupportive reactions to their children's negative emotion expression (a = .92).…”
Section: Maternal Responses To Child Emotionsmentioning
confidence: 99%